Analisis Faktor-Faktor Yang Mempengaruhi Organizational Citizenship Behavior Pegawai Dinas Pendidikan dan Kebudayaan Kabupaten Kolaka - Almansyah Rundu Wonua (JMK (Jurnal Manajemen dan Kewirausahaan), 2020)
This study aims at determing the effect transformational leadership style and job satisfaction toward Organizational Citizenship Behavior of employees Dinas Pendidikan dan Kebudayaan Kabupaten Kolaka.This research uses quantitative methods. The data used in this study consisted of primary data and secondary data. Looking at a relatively small population of 96 people, the researchers used population studies. Data analysis techniques used Structural Equation Model (SEM) assisted with SmartPLS (Partial Least Square) program. The results of the study concluded that the transformational leadership style and job satisfaction variables affect the Organizational Citizenship Behavior of employees at the Dinas Pendidikan dan Kebudayaan Kabupaten Kolaka